Naparima Company Limited: beyond the financing crunch. Issue 2 (5th May 2016) - Bowrin, Anthony Roger; Kickham, Lawrence; Krupp, Stacie L.
Abstract : Synopsis: Naparima Company Limited (NCL) was an importer and wholesaler of grocery and household products in Trinidad and Tobago, West Indies. Following increasing competition and the adoption of more lavish lifestyles by its owners, the company had fallen on hard times. Its banker, First Republic Bank, had called its outstanding loans of $1.412 million and given the company 90 days to repay all sums outstanding. Also, several major creditors had threatened legal action to recover amounts payable. This had forced NCL to explore alternative financing arrangements and to devise strategies that would improve its financial situation. Research methodology: The authors used both field interviews and secondary data when preparing this case. One of the authors was a consultant to the company as it worked to develop a restructuring plan. The primary data gleaned from that process, which included interviews with all three leaders of NCL and a review of the company's financial statements, was supplemented by the collection of secondary data about the industry and its competitors from interviews with the executive director of industry association, and information about the national economic environment from newspaper articles and library resources. Relevant courses and levels: This case is suitable for senior-level undergraduate students in a capstone business course, and graduate students in small business management and family business management courses.